In Vitro Antioxidant and Hepatoprotective Activity of Flavonoids and Flavonoid Fractions of Scoparia Dulcis L. - Sharma, Abhishek; Jain, Priya; Singh Saluja , Manmeet (Journal of Biomedical and Pharmaceutical Research, 2023)
Scoparia dulcis L. is widely used in the traditional system of medicine for treating liver ailments. In the present study the flavonoids and flavonoid fractions isolated from 9:1 Ethyl acetate and methanol (EAM) extract of Scoparia dulcis L. were tested for their in vitro 1, 1- Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity. Selected samples from the assay were further tested for their in vitro hepatoprotective activity against CCl4 induced hepatotoxicity in freshly isolated rat hepatocytes. In the in vitro antioxidant study, fractions 2, 4, and 9 and EAM extract show the DPPH radical scavenging activity. The phytochemical screening of all these fractions shows the presence of flavonoids. In the in vitro hepatoprotective study all these fractions and the EAM extract significantly prevent the CCl4 induced changes in the aspartate aspartate amino transferase, alanine amino transferase and alkaline phosphatase levels (p < 0.05). The above results are comparable with the standard, silymarin. The results of the study indicate that, the EAM extract of Scoparia dulcis L. possesses potential hepatoprotective activity and this may be attributed to its free radical scavenging potential, which in turn may be attributed to the presence of flavonoids.